2015
DOI: 10.1016/j.bbamcr.2015.05.026
|View full text |Cite
|
Sign up to set email alerts
|

JMJD5 interacts with p53 and negatively regulates p53 function in control of cell cycle and proliferation

Abstract: JMJD5 is a Jumonji C domain-containing demethylase/hydroxylase shown to be essential in embryological development, osteoclastic maturation, circadian rhythm regulation and cancer metabolism. However, its role and underlying mechanisms in oncogenesis remain unclear. Here, we demonstrate that JMJD5 forms complex with the tumor suppressor p53 by interacting with p53 DNA-binding domain (DBD), and negatively regulates its activity. Downregulation of JMJD5 resulted in increased expression of multiple p53 downstream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 36 publications
0
24
1
Order By: Relevance
“…The results demonstrated that the protein expression levels of p53 and p21 were significantly decreased following resveratrol treatment. Previous studies have indicated that p53 serves an important role in determining the response of cells to different types and levels of stressful stimuli, and regulates downstream cell cycle, cell metabolism, DNA repair and apoptotic signaling pathways (23)(24)(25). In addition, p53 regulates the expression of downstream targets, including p21, which contributes to the modulation of cell cycle progression (26).…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that the protein expression levels of p53 and p21 were significantly decreased following resveratrol treatment. Previous studies have indicated that p53 serves an important role in determining the response of cells to different types and levels of stressful stimuli, and regulates downstream cell cycle, cell metabolism, DNA repair and apoptotic signaling pathways (23)(24)(25). In addition, p53 regulates the expression of downstream targets, including p21, which contributes to the modulation of cell cycle progression (26).…”
Section: Discussionmentioning
confidence: 99%
“…32 However, in lung, colon and breast cancers, JMJD5 functions as a putative oncogene that promotes cancer cell proliferation, invasion and cellular metabolism. [29][30][31]47 In the present study, we found that JMJD5 depletion increases the susceptibility of cancer cells to microtubule-destabilizing agents by modulating microtubule stability. A recent study revealed that JMJD5 promotes cancer cell proliferation primarily by inhibiting the nuclear accumulation of p53.…”
Section: Discussionmentioning
confidence: 95%
“…A recent study revealed that JMJD5 promotes cancer cell proliferation primarily by inhibiting the nuclear accumulation of p53. 47 In addition, p53 has been reported to localize to microtubules and to undergo nuclear transport via dynein in response to DNA damage. 48 Treatment with low concentrations of microtubule-destabilizing agents, such as nocodazole, vincristine and colchicine, enhanced p53 nuclear translocation and p53-mediated activation of downstream target genes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the effects of JMJD5 on mitosis likely rely on a noncatalytic activity of JMJD5. Coincidentally, a recent report by Huang et al (43) shows that the enzymatic activity of JMJD5 is not required for its cell cycle regulation in A549 cells. However, we have found that mutant JMJD5 also mostly located in the nucleus in interphase cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%